Zmiany efektywności gospodarowania w gospodarstwach indywidualnych prowadzących rachunkowość - Bereżnicka, Joanna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1995)
This is an analysis of forming effectiveness on farms carrying agricultural bookkeeping in the years 1989-1995. As farm effectiveness measures u sed were gross final production, direct surplus and agricultural income from farms varying in size. It shows that smaller farms bad better production per 1 ha of arable land than bigger farms. This was due to bad proportion of prices of products to agricultural production outlays. Prices of products went up slower than those of production outlays. Bigger farms used considerably the purchase measures. The liquidity was also analysed for farms examined. On bigger farms the main farm activity was one the main sources of money. Whereas on smaller farms, money was earned outside the farm and provided by pensions of older family members. In these farms main expenses are for consumption whereas very little for accumulation.